Bryofloristic diversity of the Puente de Ojuela tourist area, in the sierra of Mapimí, Durango, Mexico. - Duarte-Hernández, Mario Fernando; Muro-Pérez, Gisela; Estrada-Castillón, Eduardo; Sánchez-Salas, Jaime (Ecosistemas y Recursos Agropecuarios, 2023)
Bryophytes are taxa mainly related to sites with water availability, however, in areas with limited water resources they are present in regions such as the semi-arid area of Durango; Therefore, considering that these types of ecosystems are generators of endemisms, it will be possible to find endemic species for the region of interest to science. Bryophyte mats collected along an altitude gradient in a tourist area called Puente de Ojuela were identified and their habitat preference was additionally established. A total of 17 species of bryophytes were identified in an altitudinal range from 1353 to 1850 m.a.s.l., which showed that as altitude increased, the diversity of bryophytes did so proportionally. Seven species of bryophytes were recorded for the arid and semi-arid zone of Durango. The bryofloristic diversity in the semi-arid region of Durango from the Puente de Ojuela, increases according to the altitude increase, rather than with the direct presence of the water resource. In this sense, the gap on the knowledge of said diversity is covered. Similarly, the study is considered essential for new lines of research involving the Bryophyta taxa in semi-arid environments.
Keywords: Bryophytes, altitudinal gradient, habitat preference, arid and semi-arid zones